2020
DOI: 10.1136/bcr-2020-239269
|View full text |Cite
|
Sign up to set email alerts
|

Late presentation of ‘Lemierre’s syndrome’: how a delay in seeking healthcare and reduced access to routine services resulted in widely disseminatedFusobacterium necrophoruminfection during the global COVID-19 pandemic

Abstract: The SARS-CoV-2 outbreak has disrupted the delivery of routine healthcare services on a global scale. With many regions suspending the provision of non-essential healthcare services, there is a risk that patients with common treatable illnesses do not receive prompt treatment, leading to more serious and complex presentations at a later date. Lemierre’s syndrome is a potentially life-threatening and under-recognised sequela of an oropharyngeal or dental infection. It is characterised by septic embolisation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 10 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…Fear of nosocomial SARS-CoV-2 infection may limit medical facilities attendance. Delayed diagnoses and increased disease severity have already been reported in an adult with LS (29) and in children with various conditions (30). This underlines a specificity of pediatric neurology, in which clinical examination of children with acute symptoms remains of utmost importance, and reminds us about the limits of telemedicine in acute settings.…”
Section: Discussionmentioning
confidence: 79%
“…Fear of nosocomial SARS-CoV-2 infection may limit medical facilities attendance. Delayed diagnoses and increased disease severity have already been reported in an adult with LS (29) and in children with various conditions (30). This underlines a specificity of pediatric neurology, in which clinical examination of children with acute symptoms remains of utmost importance, and reminds us about the limits of telemedicine in acute settings.…”
Section: Discussionmentioning
confidence: 79%
“…Reported risk factors for Fusobacterium bacteremia include immunosuppression, alcohol abuse, malignancy, older age, dialysis, and hospital acquired [ 17 ]. Moreover, Fusobacterium nucleatum has been shown to be associated with liver involvement [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of characteristic neck symptoms or a negative initial neck ultrasound exam does not rule out LS [ 20 ]. Case studies have demonstrated metastatic infections in the lung and brain including meningitis that also a complicated hospital course that require aggressive management and therapies [ 21 , 22 , 18 ]. Another case study demonstrated patient with LS showing septic arthritis of right shoulder, as well as parapharyngeal abscess extending from base of skull to thoracic inlet, complicated by right IJV and subclavian vein thrombosis, and multiple lung emboli [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identified themes can assist healthcare organizations with future planning to address such concerns, while specific routine care delivery processes and procedures will be dependent upon organization type and other inherent organizational characteristics. Management of chronic conditions [ 13 , 23 , 25 , 35 ], obstetrical care [ 9 , 31 ] and other routine care [ 14 , 18 , 21 , 26 ] have been identified as successful routine care delivery services continued during COVID-19. Still, a recognized backlog of delayed routine care will require additional industry initiatives and adaptations as vaccinations continue to be administered and the pandemic eventually subsides.…”
Section: Discussionmentioning
confidence: 99%